Interpretasi Tafsir dalam Konteks Modern: Tantangan dan Peluang - Dedi Kuswandi; Yosep Heristyo Endro Baruno; Nasrul Fauzi (ejournal.nurulqadim.ac.id, 2025)
This study examines the challenges faced in the interpretation of the Qur'an concerning social, political, and economic issues in the contemporary world, and how modern tafsir can provide answers to these issues. The aim of this research is to develop a tafsir model that is relevant to the realities of the modern age, using hermeneutical and linguistic approaches. The method used is library research, analyzing books, articles, and related journals. The findings show that contextual contemporary tafsir can address global challenges such as human rights, pluralism, and democracy. This research contributes to the development of a more inclusive and practical tafsir in the lives of contemporary Muslims.